Phylogenetic Study Of Genus Spathoglottis Blume (Orchidaceae) In Malesia - Nordin, Farah Alia (2018)
The genus Spathoglottis Blume (tribe Collabieae, subfamily Epidendroideae) is a genus with a total of 49 terrestrial geophyte species and is widely distributed in tropical and subtropical Asia and the Pacific Islands. A total of 44 species were recorded in the Malesian region and are concentrated particularly in New Guinea. Despite of being popular in horticulture, Spathoglottis is a taxonomically confused genus in Orchidaceae. For example, confusion is detected between a pair of species within the yellow-flowered Spathoglottis; the S. aurea and S. microchilina with both species show a complex morphological plasticity.